Interview with Dr Anil K. Khandelwal: Leading Transformation of a Public Sector Bank Through People Processes and Building Intangibles. (June 2020) - Panda, Abinash
Abstract: Dr Anil K. Khandelwal, former Chairman and Managing Director of Bank of Baroda (BoB) is credited with transforming the bank, one of the largest public sector banks, from a declining brand into a prime brand in the banking sector of India within just 3 years. Such a rapid and radical transformation using people processes by a human resource (HR) professional catapulted to chief executive officer (CEO) position is a rare example in the corporate world. In this interview, he describes the transformation journey he led, including how he overcame the challenges arising from trade union resistance to technology-led change and institutionalised people-centric business process reengineering in the new age of agile, digital banking. He describes his leadership style as "tough love" and expands on the leadership ideas he canvassed in his two books on the subject.